'Between think big and hit hard' exploring the role of teacher agency in becoming action researchers: the Egyptian context. Issue 1 (1st January 2023) - Emam, Mahmoud Mohamed; Hilal, Yara Yasser; Mohamed, Nora; Al-Mahdy, Yasser F. Hendawy
ABSTRACT: The study examined how teacher agency is manifested in Egyptian schools, how action research is perceived, and to what extent school contextual factors support or restrict teachers' agency to become action researchers. Interviews with 40 teachers from schools in northern and southern Egypt were conducted and analysed using the thematic analysis approach. Data were coded to build theoretical themes that describe Egyptian teachers' agency for action research. The study uses the ecological framework for teacher agency and the context of professional learning as conceptual tools to gain insight into teacher agency for action research. Results showed that teacher agency is defined in terms of teacher activeness rather than teacher critical discourse; teachers exercise agency as either internalizing or externalizing; teachers have a restricted agency for action research, action research is dependent on the teacher's identity commitment; teachers exercise adaptive agency in a dispirited school context; and, finally, that schools lack the collective agency for action research.